Pengaruh Job Embeddedness, Kepuasan Kerja dan Komitmen Organisasi terhadap Turnover Intention Karyawan PT. ABC - Audry Risaldy; Denta Ananda (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to test and analyze the effect of job embeddedness, job satisfaction and organizational commitment on employee turnover intention at PT ABC. The study was conducted on 91 employees of PT ABC using purposive sampling technique through questionnaire data collection using a 5-point Likert scale. The results in this study shows that job embeddedness and organizational commitment had no effect on employee turnover intention and job satisfaction had a significant negative effect on employee turnover intention